If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(8x + -4) = 44x Reorder the terms: 5(-4 + 8x) = 44x (-4 * 5 + 8x * 5) = 44x (-20 + 40x) = 44x Solving -20 + 40x = 44x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-44x' to each side of the equation. -20 + 40x + -44x = 44x + -44x Combine like terms: 40x + -44x = -4x -20 + -4x = 44x + -44x Combine like terms: 44x + -44x = 0 -20 + -4x = 0 Add '20' to each side of the equation. -20 + 20 + -4x = 0 + 20 Combine like terms: -20 + 20 = 0 0 + -4x = 0 + 20 -4x = 0 + 20 Combine like terms: 0 + 20 = 20 -4x = 20 Divide each side by '-4'. x = -5 Simplifying x = -5
| 2-(x+5)=4x-8 | | 3(x+8)=33 | | 6(6n+7)=7(6n+6)+5 | | 7x-x=36 | | 5w+10=0 | | 6x-5y=9 | | 16(x+2)=4(4x+1)+28 | | -20y=120 | | 6x=32-2x | | 40=18x-10x | | -3(x+5)+5x=10 | | 10x^2+7x-5=0 | | 6+x=32-x | | 9x-x=40 | | 5x+2(x+8)-6(4x-5)= | | -3x^2+7x=-10 | | 8xy+6yz-4xz-8xy= | | -47-18=13a | | -1(z-6)=-20 | | -7+8x=19x+15 | | -p=2 | | -6x+9=3x-27 | | (y+3)(y+5)= | | (3b^3+9b^2-3)+(2b^3-9b+7)= | | (15-7)x=(11+5)x | | -9=9(y+3) | | 3x+4(2-x)=4x+5 | | 4(2x)=72 | | (x^3+x^2+x+1)(5x-3)= | | 2(3+4)-6=48 | | 6x+4=24 | | 2(4x)=40 |